Current practices and future trends in cockroach allergen immunotherapy - Kavita, Reginald *; Chew, Fook Tim (Elsevier, 2023)
Purpose of review: This review evaluates the current modes of allergen-specific immunotherapy for cockroach allergens, in terms of clinical outcomes and explores future trends in the research and development needed for a more targeted cockroach immunotherapy approach with the best efficacy and minimum adverse effects.